Genotyping Genebank Collections: Strategic Approaches and Considerations for Optimal Collection Management - Noelle L. Anglin; Peter Wenzl; Vania Azevedo; Charlotte Lusty; David Ellis; Dongying Gao (Plants, 2025)
The maintenance of plant germplasm and its genetic diversity is critical to preserving and making it available for food security, so this invaluable diversity is not permanently lost due to population growth and development, climate change, or changing needs from the growers and/or the marketplace. There are numerous genebanks worldwide that serve to preserve valuable plant germplasm for humankind’s future and to serve as a resource for research, breeding, and training. The United States Department of Agriculture (USDA) National Plant Germplasm System (NPGS) and the Consultative Group for International Agricultural Research (CGIAR) both have a network of plant germplasm collections scattered across varying geographical locations preserving genetic resources for the future. Besides the USDA and CGIAR, there are germplasm collections established in many countries across the world that also aim to preserve crop and plant collections. Due to the advancement of technology, genotyping and sequencing whole genomes of plant germplasm collections is now feasible. Data from genotyping can help define genetic diversity within a collection, identify genetic gaps, reveal genetic redundancies and verify uniqueness, enable the comparison of collections of the same crop across genebanks (rationalization), and determine errors or mix-ups in genetic identity that may have occurred in a germplasm collection. Large-scale projects, such as genotyping germplasm collections, require strategic planning and the development of best practices. This article details strategies and best practices to consider when genotyping whole collections, considerations for the identity verification of germplasm and determining genetic replicates, quality management systems (QMS)/QC genotyping, and some use cases.